Kingdom of rage : the rise of Christian extremism and the path back to peace - Neumann, Elizabeth (Worthy Publishing, 2024)
A former counterterrorism official explores how modern evangelicalism and right-wing conservatism intermingled to form the combustible ideology that resulted in the January 6 attacks on the Capitol--and which threatens to destroy the American Church from within. In Kingdom of Rage, Neumann explores the forces within American society that have encouraged the radicalization of white supremacist, anti-government and other far-right terrorists by co-opting Christian symbols and culture and perverting the faith's teachings. While Neumann offers decades of insights into the role government policies can play to prevent further bloodshed, she believes real change must come from the within the Christian church. She shines a bright light on the responsibility of ordinary Americans - and particularly American Christians - to work within their families and their communities to counteract the narrative of victimization and marginalization within American evangelicalism. Her goal for this book is not only to sound a warning about one of the greatest threats to our security but to rescue the Church from the forces that will, if left unchecked, destroy it - culturally, morally, and ultimately quite literally. This is a book for anyone who wants to understand the unholy marriage of right-wing politics and Christian exceptionalism in America and who wants to be a part of reversing the current path towards division, hatred, violence and the ultimate undermining of both evangelical Christianity and American democracy.